Public Awareness of the Scientific Consensus on Climate. (November 2016) - Hamilton, Lawrence C.
Questions about climate change elicit some of the widest political divisions of any items on recent U.S. surveys. Severe polarization affects even basic questions about the reality of anthropogenic climate change (ACC), or whether most scientists agree that humans are changing the Earth's climate. Statements about scientific consensus have been contentious among social scientists, with some arguing for consensus awareness as a "gateway cognition" that leads to greater public acceptance of ACC, but others characterizing consensus messaging (deliberate communication about the level of scientific agreement) as a counterproductive tactic that exacerbates polarization. A series of statewide surveys, with nationwide benchmarks, repeated questions about the reality of ACC and scientific consensus many times over 2010 to 2016. These data permit tests for change in beliefs and polarization. ACC and consensus beliefs have similar trends and individual background predictors. Both rose gradually by about 10 points over 2010 to 2016, showing no abrupt shifts that might correspond to events such as scientific reports, leadership statements, or weather. Growing awareness of the scientific consensus, whether from deliberate messaging or the cumulative impact of many studies and publicly engaged scientists, provides the most plausible explanation for this rise in both series. In state-level data, the gap between liberal and conservative views on the reality of ACC did not widen over this period, whereas the liberal–conservative gap regarding existence of a scientific consensus narrowed.